Effect of Intravitreal Ranibizumab in the Treatment of Peripapillary Choroidal Neovascularisation - Hassan Hamoudi; Torben Lykke Sørensen (Journal of Ophthalmology)
Intravitreal ranibizumab therapy is widely used in treatment of subfoveal choroidal neovascularisation (CNV) in age-related macular degeneration. We wanted to study the effect of intravitreal ranibizumab therapy in peripapillary CNV. A prospective recording of treatment outcomes in twelve eyes (12 patients) with peripapillary CNV with intravitreal injections of ranibizumab was performed. The patients received a series of 3 injections 4–6 weeks apart, and then a new ophthalmic examination was made including OCT and further therapy was given if the peripapillary CNV was still active. Nine patients had idiopathic peripapillary CNV, and in 3 patients it was associated to age-related macular degeneration. Followup had to be at least 6 months. The mean follow-up time was 15.9 (range 9–27) months and the mean number of injections 6.2 (3–10). In 10 patients treatment had resulted in an inactivation of the peripapillary CNV, but 3 of them had reactivation, while 2 patients had no inactivation. Currently, 5 patients are continuous to receive treatment. VA improved in 10 patients. Intravitreal ranibizumab therapy appears to be effective in patients with peripapillary CNV, but in some cases there is repeated reactivation or continuous activity of the peripapillary CNV.